1993
DOI: 10.1254/jjp.61.137
|View full text |Cite
|
Sign up to set email alerts
|

Chronopharmacokinetic Study of a New Immunosuppressive Agent, FK 506, in Mice

Abstract: ABSTRACT-Chronopharmacokinetic profiles of a new immunosuppressive agent, FK 506, were examined in mice. FK 506 (1 mg/kg) was given orally at 10 AM (day trial) or 10 PM (night trial) once a day for 7 days. Blood samples for measurement of FK 506 concentration in whole blood were obtained just before and at 1, 2, 3, 4, 6, 8 and 12 hr after the final dosage. The time to maximum concentration was shorter and the max imum concentration was greater in the night trial than in the day trial. These findings suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…In past reports, no difference in dosing timedependent pharmacokinetics was found, which agrees with the present study (38). On the other hand, many reports have demonstrated that the blood concentration of TAC shows daily variations in which its C max is markedly increased in the active phase compared with the inactive phase (27,39,40). The main difference between these reports and our study was the route of administration.…”
Section: Discussionsupporting
confidence: 90%
“…In past reports, no difference in dosing timedependent pharmacokinetics was found, which agrees with the present study (38). On the other hand, many reports have demonstrated that the blood concentration of TAC shows daily variations in which its C max is markedly increased in the active phase compared with the inactive phase (27,39,40). The main difference between these reports and our study was the route of administration.…”
Section: Discussionsupporting
confidence: 90%
“…However, it is unclear whether similar AUC between daytime and night- time brings the best clinical outcome since animal experiments have demonstrated that tacrolimus toxicity depends on the dosing time. [27][28][29] MMF was coadministered with tacrolimus twice a day in all patients from 2 days before renal transplantation, but this did not significantly alter tacrolimus pharmacokinetics. 30,31 Gastrointestinal events such as diarrhea raise the tacrolimus concentration, 32 and while the use of MMF often results in diarrhea, there were no such events during the blood-sampling period of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In Group 1 total ACR were 12 (35.3%); in Group 2 total ACR were 27(24.1%); and in Group 3 total ACR were 5(15.2%). This is shown in Table 15 [101][102][103][104][105]. Banff grading of these rejection episodes showed that grade 2 and grade 3 rejection were absent in Group 3, as seen clearly in Table 16 [105][106][107][108][109][110].…”
Section: Rejectionsmentioning
confidence: 90%